2023
DOI: 10.1101/2023.02.20.529330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal remapping induced by new behavior is mediated by spatial context

Abstract: The hippocampus plays a central role in episodic memory and spatial navigation. Hippocampal neurons form unique representational codes in different spatial environments, which may provide a neural substrate for context that can trigger memory recall or enable performance of context-guided memory tasks. However, new learning often occurs in a familiar location, requiring that location's representation to be updated without erasing the previously existing memory representations that may be adaptive again in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…We now consider how using multi-task experiment designs can help to investigate questions of interest within and between these different theoretical frameworks. In the spatial domain, in rats, using multiple tasks in the same spatial area has been used to investigate the activity of place cells across different tasks, showing that while place cells maintain their representation across different navigation tasks (Trullier et al, 1999), changes in memory and/or attentional demands can induce remapping (Hallock & Griffin, 2013;Levy & Hasselmo, 2023;Markus et al, 1995). Similarly, by using two tasks in the same location, it has been shown that adding an associative memory task changes the representation of space in the monkey hippocampus (Gulli et al, 2020).…”
Section: Section 3: Examples Of Multi-task Research Designsmentioning
confidence: 99%
“…We now consider how using multi-task experiment designs can help to investigate questions of interest within and between these different theoretical frameworks. In the spatial domain, in rats, using multiple tasks in the same spatial area has been used to investigate the activity of place cells across different tasks, showing that while place cells maintain their representation across different navigation tasks (Trullier et al, 1999), changes in memory and/or attentional demands can induce remapping (Hallock & Griffin, 2013;Levy & Hasselmo, 2023;Markus et al, 1995). Similarly, by using two tasks in the same location, it has been shown that adding an associative memory task changes the representation of space in the monkey hippocampus (Gulli et al, 2020).…”
Section: Section 3: Examples Of Multi-task Research Designsmentioning
confidence: 99%
“…We now consider how using multi-task experiment designs can help to investigate questions of interest within and between these different theoretical frameworks. In the spatial domain, in rats, using multiple tasks in the same spatial area has been used to investigate the activity of place cells across different tasks, showing that while place cells maintain their representation across different navigation tasks (Trullier et al, 1999), changes in memory and/or attentional demands can induce remapping (Hallock & Griffin, 2013;Levy & Hasselmo, 2023;Markus et al, 1995). Similarly, by using two tasks in the same location, it has been shown that adding an associative memory task changes the representation of space in the monkey hippocampus (Gulli et al, 2020) findings in rats showed "place cells," which activate whenever the animal is in a particular location in space relative to the external environment (Moser et al, 2017;O'Keefe & Dostrovsky, 1971).…”
Section: Examples Of Multi-task Research Designsmentioning
confidence: 99%